2016
DOI: 10.1093/jhps/hnw034
|View full text |Cite
|
Sign up to set email alerts
|

Lateral acetabular coverage as a predictor of femoroacetabular cartilage thickness

Abstract: To investigate the correlation between femoroacetabular cartilage thickness and lateral acetabular coverage in patients undergoing hip arthroscopy for a variety of indications. Articular cartilage at the hip is hypothesized to undergo adaptive change secondary to unique patterns of pathomechanical loading which results in a direct relationship between acetabular coverage and femoroacetabular cartilage thickness. A cohort of 252 patients presenting to our dedicated hip preservation service between June 2013 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…In addition to labral hypertrophy, femoroacetabular cartilage hypertrophy has been identified as a sign of hip dysplasia. 3,32 In a study of 252 patients presenting to a hip preservation service, Ashwell et al 3 examined preoperative MRI scans and found an inverse correlation between the femoroacetabular cartilage thickness and the degree of lateral acetabular bony coverage ( P < .001). Furthermore, a significant difference was found in cartilage thickness among patients with normal acetabular coverage (LCEA = 25°-40°), BHD (LCEA = 20°-24.9°), and frank dysplasia (LCEA <20°) ( P < .001 for all pairwise comparisons).…”
Section: Hip Joint Morphologymentioning
confidence: 99%
“…In addition to labral hypertrophy, femoroacetabular cartilage hypertrophy has been identified as a sign of hip dysplasia. 3,32 In a study of 252 patients presenting to a hip preservation service, Ashwell et al 3 examined preoperative MRI scans and found an inverse correlation between the femoroacetabular cartilage thickness and the degree of lateral acetabular bony coverage ( P < .001). Furthermore, a significant difference was found in cartilage thickness among patients with normal acetabular coverage (LCEA = 25°-40°), BHD (LCEA = 20°-24.9°), and frank dysplasia (LCEA <20°) ( P < .001 for all pairwise comparisons).…”
Section: Hip Joint Morphologymentioning
confidence: 99%
“…Articular cartilage thickness has also been shown to exhibit hypertrophy, particularly in the acetabular roof, in newborns with DDH 13,14 . Adults with borderline or frank dysplasia show a similar trend of femoroacetabular cartilage hypertrophy 15 , which is thought to arise as a compensatory mechanism to weight-bearing and sheer stress. The same may be seen in pediatric patients with DDH after hip reduction by decreasing the medially directed force of the femoral head into the acetabulum 13 .…”
Section: Hip Instability: a Review Of Hip Dysplasia And Other Contribmentioning
confidence: 99%
“…Lateral acetabular coverage correlates with femoroacetabular cartilage thickness, which indicates that the cartilage may transform under certain circumstances. In dysplastic hips, the cartilage at the lateral part was 35% thicker compared with the hips with normal acetabular coverage, suggesting that the hip morphologically changes in response to abnormal joint loading ( 65 ). One study showed a more prominent T2 signal decrease in the outer superficial acetabular cartilage of dysplastic hips during weight loading in comparison with normal hips.…”
Section: Radiological Characteristics Of the Articular Cartilage In Dmentioning
confidence: 99%